2005
DOI: 10.1186/cc3806
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Introduction Acute metabolic acidosis of non-renal origin is usually a result of either lactic or ketoacidosis, both of which are associated with a high anion gap. There is increasing recognition, however, of a group of acidotic patients who have a large anion gap that is not explained by either keto-or lactic acidosis nor, in most cases, is inappropriate fluid resuscitation or ingestion of exogenous agents the cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 119 publications
(34 citation statements)
references
References 22 publications
4
27
0
2
Order By: Relevance
“…In our study we found that the level of hydroxybutyrate increased significantly by almost twenty times in those with diabetes, but that the level of citrate did not differ significantly when compared to control values. It is widely reported elsewhere that plasma citrate is generally not elevated in acidosis [8,9], and we confirmed this in a previous study [1] as well as the results reported above.…”
Section: Discussionsupporting
confidence: 95%
See 3 more Smart Citations
“…In our study we found that the level of hydroxybutyrate increased significantly by almost twenty times in those with diabetes, but that the level of citrate did not differ significantly when compared to control values. It is widely reported elsewhere that plasma citrate is generally not elevated in acidosis [8,9], and we confirmed this in a previous study [1] as well as the results reported above.…”
Section: Discussionsupporting
confidence: 95%
“…Despite this, in clinical settings only lactate is routinely measured. We have previously shown that, in certain acidotic states, the level of circulating anions normally associated with intermediary metabolism are elevated and make a significant contribution towards the anion load that has previously been overlooked [1]. Although enzymatic methods exist to measure the absolute quantities of anions in the plasma, these methods are slow, cumbersome and provide a degree of accuracy that is very often unnecessary in clinical settings where a measurement of the absolute amount of an anion is often of secondary importance to its relative amounts and/or presence.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…33 Succinate accumulation might mediate platelet over-activation and thus potentiate untoward hypercoagulation in trauma patients. 34 Concomitant accumulation of lactate and TCA intermediates is suggestive that early metabolic alterations following trauma promote channeling to the TCA cycle of additional carbon substrates other than sugars, such as lipids and proteins.…”
Section: Discussionmentioning
confidence: 99%